An Application of HVSR Method on Microtremor Data for Analysis of Earthquake Potential in Candipuro District, Lumajang, Indonesia - Yatini, Y.; Kustanto Putra, Abdurrohim; Paripurno, Eko Teguh (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
The Earthquake of 6.1 magnitude occurred on April 10, 2021, in Lumajang district. One affected area suffered building losses, road damage, and casualties in Candipuro District, Lumajang Regency, East Java. Then the research was conducted to determine the strength of the soil against the potential earthquake by micro zoning the area in Candipuro District. This research uses the microtremor method with HVSR (Horizontal to Vertical Spectral Ratio) analysis. Analysis of earthquake potential includes parameters of Ground Amplification (A0), Dominant Frequency (f0), Ground Vulnerability Index (Kg), and Ground Shear Strain (GSS). The acquisition was completed with 16 measurement points in Supiturang Village with 500 meters between points using the Portable Seismograph TDS - 303. The results obtained in Supiturang Village have the results of the amplification value factor which is classified as medium-high (2.7 - 8.7), low dominant frequency value (0.5 - 1.4 Hz), medium-high soil susceptibility index (10 - 90), VS30 value which includes medium - hard soil (187.81 - 548.38) m/s, and GSS value which shows the response of cracks and soil subsidence to shaking (2 x 10-5 - 2 x 10-4).